PERAN PEMANGKU KEPENTINGAN DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI - Krisna, Eko; Panjaitan, Poltak BP; Salampessy, Messalina L (Universitas Nusa Bangsa, 2015)
A watershed is a natural resource management unit, in which there are resources that are managed by the government, private, and community. The role of the various stakeholders, helped influence on changes in the physical characteristics of the watershed. The existence and role of the various stakeholders in a watershed to be important in restoring watershed ecosystem function and maintain watershed conditions. For that, this study aims to examine the role of stakeholders and power relations that exists in the management of Hulu Cisadane subzone. Data was collected by in-depth interviews and field observations and study of literature. Analisisi data were analyzed descriptively. The results showed that the position and role of stakeholders kepentigan namely Instasi government, private and Peoples, which is categorized as a group decision (appropriator), providers and the producent, where the role of these stakeholders still overlap led to weak policies interference with the watershade function.